Analisis Beban Kerja Mental saat Mengoperasikan Smartphone dengan Memperhatikan Postur Tubuh: Pendekatan Menggunakan Metode NASA-TLX - Kurnia, Fikrihadi (Fakultas Teknik Universitas Tulang Bawang, 2024)
Work physiology is the study of understanding how the human body adapts and functions in the work environment. Occupational physiology involves the study of the body's physiological responses to work-related demands and stress. This understanding is necessary to protect workers' health and welfare, as well as increase work productivity and efficiency. This research aims to analyze physiological workload by focusing on measuring mental workload, using the NASA-TLX method. Research activities were carried out on 12 students from the Department of Industrial Engineering, Universitas Mataram. Students were divided into 3 groups according to their assigned work posture, namely standing (Group A), sitting (Group B), and lying down (Group C). The results showed that the order of subjects with the highest mental workload was subject 1A (78.97%) with a standing posture, 2B (77.33%) with a sitting posture, and 4A (73.57%) with a standing posture. Based on these results, the final conclusion that can be drawn is that the mental workload in standing and sitting postures is what is most felt by the subject when operating the smartphone. These results conclude that different postures when operating a smartphone can affect the user's mental workload Keywords: Mental, NASA-TLX, Posture, Smartphone, Workload.